2015
DOI: 10.4103/0975-7406.155937
|View full text |Cite
|
Sign up to set email alerts
|

Management of tripod fractures (zygomaticomaxillary complex) 1 point and 2 point fixations: A 5-year review

Abstract: The zygomaticomaxillary complex (ZMC) plays a key role in the structure, function, and esthetic appearance of the facial skeleton. They can account for approximately 40% of mid-face fractures. They are the second most common facial bone fracture after nasal bone injuries. The fracture complex results from a direct blow to the malar eminence and results in three distinct fracture components that disrupt the anchoring of the zygoma. In addition, the fracture components may result in impingement of the temporalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…18 Balakrishnan from India also reported age group 20 to 40 being more prone to RTAs which was also concordant with our results. 19 Nerve injury following fracture may present with various pathophysiology involving traction, pressure, ischemia, inflammation and physical damage of the infra-orbital nerve resulting in sensory neuropathy and motor functions in the area of innervation of infra-orbital nerve both as presenting symptom and as a postoperative complication. 7 A study from Iran assessed the sensorimotor nerve damage in patients with maxillofacial trauma and found that infra-orbital nerve damage was the second most common nerve damaged after trigeminal.…”
Section: Discussionmentioning
confidence: 99%
“…18 Balakrishnan from India also reported age group 20 to 40 being more prone to RTAs which was also concordant with our results. 19 Nerve injury following fracture may present with various pathophysiology involving traction, pressure, ischemia, inflammation and physical damage of the infra-orbital nerve resulting in sensory neuropathy and motor functions in the area of innervation of infra-orbital nerve both as presenting symptom and as a postoperative complication. 7 A study from Iran assessed the sensorimotor nerve damage in patients with maxillofacial trauma and found that infra-orbital nerve damage was the second most common nerve damaged after trigeminal.…”
Section: Discussionmentioning
confidence: 99%
“…Resorbable plates offer one possible solution, but the ideal combination of resorbable and titanium plates in adults is still being evaluated (Hanemann et al, ) and to our knowledge there are no randomized controlled studies of their long term sequelae in children (Boyette, ). Decreasing the number of plates provides another route to decreased morbidity, and the early agreement on the advisability of using at least two mini‐plates in zygomatic fracture repair (Rinehart et al, ; Davidson et al, ) is being questioned by advocates of single plate implants (Balakrishnan et al, ).…”
Section: How Useful Is the Pillar‐buttress Concept Clinically And Canmentioning
confidence: 99%
“…[1][2][3][4] Despite the relative frequency of these injuries, there remains debate regarding management, including number of approaches and points of fixation and the decision to explore the orbital floor. [5][6][7][8][9][10][11][12][13][14] Recent studies have attempted to resolve these controversies using large cohorts to derive algorithms for management. 2,3 At many institutions, facial trauma management is divided across several services, such as oral and maxillofacial surgery, plastic and reconstructive surgery, and otolaryngology (ORL).…”
mentioning
confidence: 99%